Gambaran Perilaku Disiplin Belajar Siswa Kelas 10 SMA Negeri X di Kabupaten Sikka - Clara Beata Mona Aso; Sitti Anggraini (Mathematics Education Study Program, 2025)
The purpose of this study was to determine the description of learning discipline in 10th grade students of X State High School in Sikka Regency. This study uses descriptive quantitative research. The population in this study were all students of SMA Negeri X iwhich amounted to 1200 students. The sample in this study amounted to 354 people. Researchers took samples using non-probability sampling techniques, namely purposive sampling with criteria. The criteria determined are Class X students who show undisciplined behavior and are around 14-17 years old. The results showed that the high learning discipline category amounted to 6 people by 1.70%, the moderate learning discipline category amounted to 204 people by 57.63%, and the low learning discipline category amounted to 144 people by 40.67%. Based on the research results, it is concluded that the learning discipline of 10th grade students of SMA Negeri X in Sikka Regency is in the moderate category.